THE EFFECT OF ROAD AND IRRIGATION INFRASTRUCTURE DEVELOPMENT ON AGRICULTURAL GROSS DOMESTIC PRODUCT IN THE PROVINCE OF WEST JAVA - Rusidi Ansyari Harahap; Ma'mun Sarma; Nunung Kusnadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study is to determine the effect of infrastructure such as roads and irrigation on agricultural sector GRDP in West Java Province. The data used in this research is secondary data. The method used is classical assumption test and multiple linear regression. The results of this study indicate that the road variable has a positive and significant effect on agricultural sector GRDP, while the irrigation variable does not show significant results and has no positive effect on agricultural sector GRDP in West Java Province. Based on the results of the study in the context of economic development in the agricultural sector of West Java Province, it is directed to spur equitable distribution of irrigation development so that agricultural production increases and road infrastructure as a basis for distributing agricultural production and increasing the optimal utilization of regional potential, especially in the agricultural sub-sector in West Java Province. Thus, the government is expected to maintain the climate and build infrastructure in a sustainable manner to keep the agricultural sector growing better.